The regional-innovation cluster policy for R&D efficiency and the creative economy: With focus on Daedeok Innopolis. Issue 2 (3rd July 2017) - Yoon, Donghun
Abstract : Purpose: This paper aims to discuss and present the regional-innovation cluster policy for R&D efficiency and the creative economy. In particular, the R&D efficiency and creative economy of Daedeok Innopolis are discussed for the science and technology policy of the R&D regional-innovation cluster. In this research, the region cluster policy change, the creative innovation system construction, the manpower system construction and the support unification for R&D and commercialization are presented as policy proposals for R&D efficiency and the creative economy. Design/methodology/approach: In this research, the universities, research institutes and enterprises of Daedeok Innopolis were studied. Thirty people from the universities in the area, 30 from the research institutes and 30 from the enterprises were surveyed through the quota sampling of the non-probability sampling method for this research. These survey respondents were science and technology policy specialists for the R&D, industrialization and entrepreneurial activities of Daedeok Innopolis. The methodological material is a questionnaire. The study's investigation factors were the government's role, knowledge creation and the network. Also, F-test, ANOVA and chi-square independence test were utilized for the survey data analysis. Findings: Regional-innovation cluster construction is a representative method of realizing regional development and competition enhancement. This research was found through the analysis that the government policy is very useful for innovation ecosystem development. The knowledge capability has been enhanced in connection with knowledge creation. Also, the network has been vitalized. New-dimension industry–university–institute collaboration and a human resource management system are needed for R&D efficiency and the creative economy. Daedeok Innopolis needs consistent support for industrialization and foundation. Social implications: Movement of and cooperation among humans, goods, knowledge, technologies, etc., occur in many areas (science, the economy, culture, arts, etc.) because of the compression of time and space through informatization and globalization. This has brought about changes in cross-border, regional and national relations and has stimulated competition in the aforementioned areas. To date, a state-dominated system has been operated to deal with these changes, but it has been shown to be inefficient because it cannot reflect the conditions in the region and does not allow quick reaction. The advantages of the region must be identified and utilized to boost the survival and development of the region. Regional-innovation cluster construction is a representative method of realizing regional development and competition enhancement. Originality/value: The innovative feature of the study is proposed the science and technology policy (the region cluster policy change, the creative innovation system construction, the manpower system construction and the support unification for R&D and commercialization) for the R&D regional-innovation cluster through the survey data analysis. In this paper, the R&D efficiency and the creative economy of Daedeok Innopolis are discussed for the science and technology policy of the R&D regional-innovation cluster. The science and technology policy for the R&D regional-innovation cluster development is examined for the first time in this paper. This research is expected to make a significant contribution to the establishment of a development strategy for the regional-innovation cluster, and to the decision-making regarding the science and technology policy.